One Hundred Twenty-Eight Consecutive Sleeve Gastrectomies, Short-Term Outcomes, and Impacts on Type 2 Diabetes Mellitus - YAVUZ, DİLEK (SPRINGER INDIA, 2018)
Laparoscopic sleeve gastrectomy (LSG) is becoming one of the most frequent bariatric procedures performed, though it is still related to a number of serious complications. The aim of the study was to share our experiences with LSG in terms of postoperative complications, weight loss, and their impacts on comorbidities related with obesity. We reviewed all patients who had undergone LSG and completed at least 6months follow-up in our unit from April 2012 through October 2014. Patients' characteristics, operative data, postoperative complications, weight loss, resolution and improvement rates of diabetes mellitus, and hypertension were noted. Surgical techniques and patient care were described in detail. We included 128 patients (median age 36, 76% female) in our study. Postoperative complications included one (0.8%) staple line leak, two (1.6%) postoperative bleeding requiring transfusion, and one (0.8%) pulmonary embolism. Mean follow-up time was 17 (6-38) months. Mean BMI was reduced from 47.2 +/- 6 to 32.6 +/- 6.2kg/m(2) at the end of the follow-up period. At baseline, 51 (39.8%) patients had type 2 diabetes mellitus, and 25 (19.5%) patients had hypertension. Resolution and improvement rates were 80.4 and 13.7% for type 2 diabetes mellitus and 44 and 24% for hypertension, respectively. LSG seems to be a safe and effective procedure for morbid obesity and obesity-related diseases. In order to achieve low complication rates, measures in operative techniques and intraoperative endoscopy are recommended.
Keywords: Sleeve gastrectomy; Type 2 diabetes mellitus; Complications; Intraoperative endoscopy; HIGH-RISK PATIENTS; STAPLE-LINE; METABOLIC SURGERY; EXPERIENCE; OPERATION